(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the transformative potential of modern technology in English language teaching (ELT), showcasing its impact on various aspects of learning, including vocabulary acquisition, grammar comprehension, pronunciation practice, and cultural immersion. The article highlights the benefits of utilizing various technological tools while acknowledging the challenges and considerations for effective implementation.